Quan điểm chỉnh hóa trong ước lượng và điều khiển hệ động lực - Lan, Vu Nhu; Son, Hoang Hong; Volodchenko, G.I. (Journal of Computer Science and Cybernetics, 2018)
A approach based on the regularization is suggested. This concept can be effectively applied for  solving one wide class of filtering and control problems at the uncertain conditions. The effectivety of suggested approach  is demonstrated by the case for control of stationary systems.